PRICE TRANSPARENCY ISSUES AND TREATING CUSTOMER FAIRLY BY E-COMMERCE FIRMS IN INDIA - Kumari J, Jensolin Abitha; Gotmare, Dr Preeti R (The journal of contemporary issues in business and government, 2021)
The Indian E-commerce industry is growing rapidly due to outbreak of pandemic, rapid increase in use of smartphones and access to high speed internet have resulted in customers looking for convenience by making online purchase thereby saving time and cost. Technology plays an inevitable role in helping ecommerce firms maximize their profit by analyzing customer behavior online, making recommendations and providing personalized pricing. This paper will focus of understanding and analyzing the present scenario in the online retail space to explore the following concerns which is a point of discussion in this field. Are customers really being treated fairly by ecommerce firms? Are customers guided to make purchase through recommendation engines and personalized pricing and end up paying more as firms are able to identify their willingness to pay more? This provides a qualitative study to answer these questions.